2018
DOI: 10.1038/s41366-018-0207-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of provider-prescribed obesogenic drugs on post-laparoscopic sleeve gastrectomy outcomes: a retrospective cohort study

Abstract: Background:Laparoscopic sleeve gastrectomy (LSG) is one of the most commonly performed bariatric procedures and has proven effective in providing weight loss. However, considerable variance has been noted in the degree of weight loss. Physician prescription practices may be negatively affecting weight loss post-LSG and, thus, contributing to the broad range of weight loss outcomes. The aim of our study was to determine whether commonly prescribed obesogenic medications negatively affect weight loss outcomes po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Our main conclusion is bolstered by a recent publication that showed that exposure to obesogenic medications had a significant effect on post-laparoscopic sleeve gastrectomy weight-loss outcomes. More specifically, patients on obesogenic medications lost significantly less weight 1 year after bariatric surgery compared with patients not using those drugs (53.8% of excess weight lost vs. 65.0%, respectively; P = 0.002) (26). Together, these studies show that regardless of patient population (i.e., predominantly male veterans, predominantly affluent women) and treatment modality (i.e., behavioral/dietary intervention, bariatric surgery), any exposure to obesogenic medications during treatment negatively affected weight-loss outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Our main conclusion is bolstered by a recent publication that showed that exposure to obesogenic medications had a significant effect on post-laparoscopic sleeve gastrectomy weight-loss outcomes. More specifically, patients on obesogenic medications lost significantly less weight 1 year after bariatric surgery compared with patients not using those drugs (53.8% of excess weight lost vs. 65.0%, respectively; P = 0.002) (26). Together, these studies show that regardless of patient population (i.e., predominantly male veterans, predominantly affluent women) and treatment modality (i.e., behavioral/dietary intervention, bariatric surgery), any exposure to obesogenic medications during treatment negatively affected weight-loss outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…A similar effect of obesogenic medications was observed among patients undergoing a bariatric procedure (sleeve gastrectomy). Leggett et al (16) found that patients who were exposed to obesogenic medications had an 11.2% smaller mean percentage of excess weight loss after sleeve gastrectomy than those who were not. Their results showed that obesogenic medications interfere with weight loss significantly enough to modify the results of a behavioral intervention program as well as a bariatric procedure.…”
Section: Discussionmentioning
confidence: 99%
“…This could have resulted in underreporting of the obesogenic medication use and possible misclassification bias. Also, the list of obesogenic medications was not as comprehensive as other studies that focused on obesogenic medications (15,16). Second, the exact duration and dosage of medication use were not available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high prevalence of obesity can be attributed to increased calorie intake and decreased energy expenditure, which are influenced by the availability of low-cost, energy-dense, highly palatable foods and an increasingly sedentary environment (3); however, other environmental factors such as medication use may also play a role. Many prescription medications have weight gain as an adverse and unintentional effect ("obesogenic" medications) (4,5), and the use of these medications has been recognized as a preventable cause of obesity (6). Although "obesogenic" as a term may be limited because weight gain does not always result in BMI ≥ 30 kg/m 2 , it is widely used to describe medication-induced weight gain.…”
Section: Introductionmentioning
confidence: 99%